2018
DOI: 10.1111/ceo.13129
|View full text |Cite
|
Sign up to set email alerts
|

Primary bilateral uveal melanoma: a population‐based study and systematic review

Abstract: Bilateral and unilateral UM patients share similar demographics, clinicopathological characteristics, treatments and prognoses. Moreover, the development of bilateral disease does not portend a poorer prognosis and patients should be treated similarly to those with unilateral disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In a systematic review comparing bilateral (n = 52) to unilateral uveal melanoma (n = 8,915) by Scott et al [13], the authors found no difference in overall survival between the 2 groups of patients. Scott et al [13], however, found a significant difference between the treatment methods chosen for the first and second affected eyes in bilateral melanoma. The first eye was more likely to be enucleated, while the second was more likely to be treated in a globe-sparing fashion.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a systematic review comparing bilateral (n = 52) to unilateral uveal melanoma (n = 8,915) by Scott et al [13], the authors found no difference in overall survival between the 2 groups of patients. Scott et al [13], however, found a significant difference between the treatment methods chosen for the first and second affected eyes in bilateral melanoma. The first eye was more likely to be enucleated, while the second was more likely to be treated in a globe-sparing fashion.…”
Section: Discussionmentioning
confidence: 97%
“…There is no evidence to suggest that bilateral disease portends an increased metastasis risk, the individual tumor profile notwithstanding. In a systematic review comparing bilateral ( n = 52) to unilateral uveal melanoma ( n = 8,915) by Scott et al [13], the authors found no difference in overall survival between the 2 groups of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this report by Scott et al ., a population‐based study and systematic review was performed using three sources: a pathology database from 1996 to 2016; the Surveillance, Epidemiology and End‐Results (SEER)‐18 from 1973 to 2103; and published English literature, resulting in a total of 52 cases of bilateral uveal melanoma . Genetic testing was not a part of this analysis.…”
mentioning
confidence: 99%
“…They found that survival did not differ between patients with unilateral versus bilateral uveal melanoma; however, they acknowledged that the number of bilateral cases were few. These authors astutely speculated that the observation of ‘uveal melanoma occurring in a paired organ suggests a genetic predisposition’ to developing this malignancy …”
mentioning
confidence: 99%